PRESSOR RESPONSE OF STRENGTH TRAINING IN DIFFERENT PERIODS OF THE DAY IN NORMOTENSIVE (Fiep Bulletin - online, 2011)
The research aimed to analyze the behavior of blood pressure during strength training at different times of day, i.e., in three shifts, morning, noon and night. The sample comprised 10 individuals, male, 18-30 years, normotensive, healthy and without use of any drug that may interfere with blood pressure, and had experience and knowledge in fitness, i.e., practitioners and advanced intermediates . The volunteers performed resistance exercises for the legs, into equipment, leg extension (leg extension), leg press (pressure leg), leg curl (leg curl) in a uniform fitness workout with 3 sets of 10 repetitions. The subjects answered a questionnaire before starting to run the tests and signed the informed consent (IC). Pressure was measured at rest preceding the execution of the first series and after gauging the end of the series in all units following the same order of execution of the unit for all individuals, leg extension, leg press and leg curl. The load was determined using the 1RM test, calculating 85% of the maximum load of each individual. At the end of the study we can conclude that there was a change in blood pressure at the end of the exercises, but there was no significant change at different times of day. However, our research may help to have possible studies involving the circadian cycle in various other forms of physical activity.
Keywords: 1; Blood pressure; 2; Strength training; 3; Circadian rhythm